Exploratory focused pharmacogenetic testing reveals novel markers associated with risperidone pharmacokinetics in Saudi children with autism - Shilbayeh, Sireen Abdul Rahim; Adeen, Iman Sharaf; Ghanem, Ezzeldeen Hasan; Aljurayb, Haya; Aldilaijan, Khawlah Essa; AlDosari, Fatimah; Fadda, Abeer (Frontiers in Pharmacology, 2024)
Background: Genomic studies have revealed a considerable overlap between the molecular mechanisms implicated in the aetiology of autism spectrum disorders (ASD) and genes involved in the pharmacokinetic (PK) and pharmacodynamic (PD) pathways of antipsychotic drugs employed in ASD management. Given the conflicting data originating from candidate PK or PD gene association studies, dosage individualization based on “actionable” pharmacogenetic (PGx) markers has limited application in clinical practice. This exploratory study aimed to identify PGx markers predictive of risperidone (RIS) exposure in autistic Saudi children. Methods: Prospective cohort study enrolled 89 children with ASD treated with RIS-based antipsychotic therapy. RIS and 9-OH-RIS plasma levels were measured using a liquid chromatography tandem mass spectrometry system. To enable exploratory focused testing, genotyping was performed with the Axiom Array, including a collection of probe sets targeting PK/PD genes. A total of 720 PGx were included in the association analysis. Results: A total of 27 PGx variants were identified that showed a prominent impact on various RIS PK parameters; most were not located within the genes involved in the classical RIS PK pathway. Eight markers in 7 genes were identified as the top PGx markers with a strong impact on RIS levels (P<0.01). Four variants in 3 genes were found to be strongly associated with 9-OH-RIS levels, while 5 markers in 5 different genes were found to explain the interindividual variability in the total active moiety. Of note, 6 CYP2D6 variants were in strong linkage disequilibrium; however, they only significantly influenced the metabolic ratio and had no considerable effects on the individual estimates of RIS, 9-OH-RIS, and total active moiety. After correction for multiple testing, rs78998153 in UGT2B17 remained the most significant PGx marker positively adjusting the metabolic ratio. For the first time, certain HLA markers were found to enhance various RIS exposure parameters, which reinforce the gut–brain axis theory of ASD aetiology. Conclusion: Our hypothesis-generating approach in this study identified a broad spectrum of PGx markers interactively influencing RIS exposure in ASD children, which indicated the need for further validation in population PK modelling studies to define polygenic scores for antipsychotic efficacy and safety.